Impact of Poor Oral Health on Community-Dwelling Seniors: A Scoping Review. (January 2021) - Badewy, Rana; Singh, Harkirat; Quiñonez, Carlos; Singhal, Sonica
The aim of this scoping review was to determine health-related impacts of poor oral health among community-dwelling seniors. Using MeSH terms and keywords such as elderly, general health, geriatrics, 3 electronic databases—Medline, CINAHL, and Age Line were searched. Title and abstracts were independently screened by 3 reviewers, followed by full-texts review. A total of 131 articles met our inclusion criteria, the majority of these studies were prospective cohort (77%, n = 103), and conducted in Japan (42 %, n = 55). These studies were categorized into 16 general health outcomes, with mortality (24%, n = 34), and mental health disorders (21%, n = 30) being the most common outcomes linked with poor oral health. 90% (n = 120) of the included studies reported that poor oral health in seniors can subsequently lead to a higher risk of poor general health outcomes among this population. Improving access to oral healthcare services for elderly can help not only reduce the burden of oral diseases in this population group but also address the morbidity and mortality associated with other general health diseases and conditions caused due to poor oral health. Findings from this study can help identify shortcomings in existing oral healthcare programs for elderly and develop future programs and services to improve access and utilization of oral care services by elderly.